Tragedy of Errors at Warp Speed: The 2019 Unrest - Sam Ho (Global Storytelling)
The 2019 unrest in Hong Kong was the result of complex factors simmering over the years, culminating in a tragedy of errors unreeling at warp speed. This paper examines a few of the factors from the personal perspective of a Hong Kong-born Chinese American. Since the 1997 Retrocession, Hong Kong had been engaged in a unique version of post-colonial condition, “one country, two systems” (OCTS), meaning that it must contend with not only ways of a new beginning and ways of the former days but also ways for a future beginning—that of future China when OCTS expires. Hong Kong had also been conditioned to look at itself through the Western gaze and its future through Western imagination, resulting in self-objectification. Many of its people were consumed by misguided idealism that compelled citizens toward a profound mistrust of China while turning a blind eye to the country’s unique accomplishment. A powerful media dedicated to promoting the Western agenda further fanned the fire, turning the former colony into an unwitting proxy of the new Cold War waged by the United States on China. Such was a tragedy of errors that a movement launched against a worrisome rule, resulting in the passing of a law even more worrisome.